2022
DOI: 10.33073/pjm-2022-015
|View full text |Cite
|
Sign up to set email alerts
|

Growth Behavior and Transcriptome Profile Analysis of Proteus mirabilis Strain Under Long- versus Short-Term Simulated Microgravity Environment

Abstract: Spaceflight missions affect the behavior of microbes that are inevitably introduced into space environments and may impact astronauts’ health. Current studies have mainly focused on the biological characteristics and molecular mechanisms of microbes after short-term or long-term spaceflight, but few have compared the impact of various lengths of spaceflight missions on the characteristics of microbes. Researchers generally agree that microgravity (MG) is the most critical factor influencing microbial physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…They observed reduced biofilm formation after 64 days and following transcriptional analysis proposed that this reduction was potentially due to downregulation of the pil and algR genes associated with conjugative pili and alginate biosynthesis, or upregulation of genes involved in metal iron binding (as available iron increases biofilm formation) 443 . In another study analyzing Proteus mirabilis biofilm formation following short-term or long-term SMG, researchers found that long-term exposure resulted in downregulation of genes associated with fimbriae, impeding adhesion, and ultimately decreasing biofilm formation 444 .…”
Section: Negative Impact Of Microbes and Mitigation Strategiesmentioning
confidence: 99%
“…They observed reduced biofilm formation after 64 days and following transcriptional analysis proposed that this reduction was potentially due to downregulation of the pil and algR genes associated with conjugative pili and alginate biosynthesis, or upregulation of genes involved in metal iron binding (as available iron increases biofilm formation) 443 . In another study analyzing Proteus mirabilis biofilm formation following short-term or long-term SMG, researchers found that long-term exposure resulted in downregulation of genes associated with fimbriae, impeding adhesion, and ultimately decreasing biofilm formation 444 .…”
Section: Negative Impact Of Microbes and Mitigation Strategiesmentioning
confidence: 99%
“…GO enrichment analysis of differentially expressed genes was implemented by the top GO R package, in which gene length bias was corrected [27] . GO terms with corrected p<0.05 were considered significantly enriched by differential expressed genes.…”
Section: Gene Ontology (Go) and Kyoto Encyclopedia Of Genes And Genom...mentioning
confidence: 99%